Band gap engineering of ZnO by doping with Mg. (2nd July 2015) - Rana, N; Chand, Subhash; Gathania, Arvind K
Abstract: Mg-doped zinc oxide (Mg x Zn1− x O (0 ≤  x  ≤ 0.20)) samples were synthesized by polymeric precursor method. The structural and optical properties were investigated by x-ray diffractometer (XRD), field emission scanning electron microscope (FE-SEM), UV–visible spectroscopy, Fourier transform infrared (FTIR) and Raman spectroscopy. XRD patterns reveal that synthesized samples have a wurtzite structure. Lattice parameters, the degree of distortion of the samples were calculated from the XRD. SEM images show that the synthesized samples contain the elongated spherical shaped grains. The Raman scattering investigation and FTIR spectra authenticate the presence of Mg in the system and also show phase segregation at the higher Mg doping concentration. Optical band gap energy is determined from the Tauc relation. It is interesting to know that optical band energy exhibits blue shift with the increase of Mg doping concentration up to 16 mole %.